Women's coping strategies during the first three months of adjuvant endocrine therapy for breast cancer - Susanne Ahlstedt Karlsson; Catarina Wallengren; Roger Olofsson Bagge; Ingela Henoch (Wiley, 2020)
Abstract Aim The aim was to explore stressful events, experienced problems and used coping strategies during the first three months of undergoing ET. Design This study used a mixed method design. Methods A consecutive sample of 39 women newly diagnosed with breast cancer were included at the start of their adjuvant endocrine therapy. A daily coping assessment was used to create daily reports about stressful events or experienced problems and coping strategies. Results The most frequently reported physical problems were sleeping difficulties. Anxiety was the most reported emotional problem. Patients used both emotion‐and problem‐focused coping, and sleeping difficulties were coped by relaxing, and anxiety was coped by thinking about something else. Conclusions Patients experienced a variety of stressful events or problems during the first three months of endocrine therapy. They also used several coping strategies to endure the treatment.